Modification of the existing maximum residue levels for spirotetramat in herbs and edible flowers. (12th December 2022) - ,; Bellisai, Giulia; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Castellan, Irene; Del Aguila, Monica; Ferreira, Lucien; Giner Santonja, German; Greco, Luna; Jarrah, Samira; Leuschner, Renata; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Landesanstalt für Landwirtschaft und Gartenbau (LLG) submitted a request to the competent national authority in Germany to modify the existing maximum residue levels (MRLs) for the active substance spirotetramat in herbs and edible flowers. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the group of herbs and edible flowers. Adequate analytical methods for enforcement are available to control the residues of spirotetramat and its metabolite spirotetramat‐enol on the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg for each analyte. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of spirotetramat according to the reported agricultural practice is unlikely to present a risk to consumer health.